Dinamika Tenaga Kerja Informal: Perspektif Demografi dan Ekonomi di Sulawesi Selatan - Dirmansyah Darwin; I Made Jyotisa Adi Dwipatna; Ahmad Fadhil Imran; Hafid Sumarwadji; Muhammad Yamin (Department of Management - Institut Shanti Bhuana, 2025)
This study aims to analyze the influence of demographic and economic variables on the absorption of informal labor in South Sulawesi Province. The approach used is quantitative, employing multiple linear regression analysis on panel data from 24 regencies/cities during the period of 2020–2024. The independent variables analyzed include the Labor Force, Youth Population (NEET), and Gross Regional Domestic Product (GRDP). The results show that, partially, only the Labor Force variable has a positive and significant effect on the absorption of informal labor. On the other hand, Youth Population and GRDP do not show significant effects. However, simultaneously, all three variables have a significant impact on informal labor absorption, as demonstrated by the F-test. The coefficient of determination (R²) value of 0.846 indicates that 84.6% of the variation in informal labor absorption can be explained by the model. These findings highlight the importance of addressing labor force dynamics and demographic structure in designing inclusive and sustainable labor policies, particularly for the informal sector, which is a major pillar of the local economy in South Sulawesi.